Nonsense codons in human beta-globin mRNA result in the production of mRNA degradation products. - Lim, S K (1992)
Human beta zero-thalassemic beta-globin genes harboring either a frameshift or a nonsense mutation that results in the premature termination of beta-globin mRNA translation have been previously introduced into the germ line of mice (S.-K. Lim, J.J. Mullins, C.-M. Chen, K. Gross, and L.E. Maquat, EMBO J. 8:2613-2619, 1989). Each transgene produces properly processed albeit abnormally unstable mRNA as well as several smaller RNAs in erythroid cells. These smaller RNAs are detected only in the cytoplasm and, relative to mRNA, are longer-lived and are missing sequences from either exon I or exons I and II. In this communication, we show by using genetics and S1 nuclease transcript mapping that the premature termination of beta-globin mRNA translation is mechanistically required for the abnormal RNA metabolism. We also provide evidence that generation of the smaller RNAs is a cytoplasmic process: the 5' ends of intron 1-containing pre-mRNAs were normal, the rates of removal of introns 1 and 2 were normal, and studies inhibiting RNA synthesis with actinomycin D demonstrated a precursor-product relationship between full-length mRNA and the smaller RNAs. In vivo, about 50% of the full-length species that undergo decay are degraded to the smaller RNAs and the rest are degraded to undetectable products. Exposure of erythroid cells that expressed a normal human beta-globin transgene to either cycloheximide or puromycin did not result in the generation of the smaller RNAs. Therefore, a drug-induced reduction in cellular protein synthesis does not reproduce this aspect of cytoplasmic mRNA metabolism. These data suggest that the premature termination of beta-globin mRNA translation in either exon I or exon II results in the cytoplasmic generation of discrete mRNA degradation products that are missing sequences from exon I or exons I and II. Since these degradation products appear to be the same for all nonsense codons tested, there is no correlation between the position of translation termination and the sites of nucleolytic cleavage.